ANALISIS KESEJAHTERAAN RUMAH TANGGA PETANI PADI SAWAH BERDASARKAN PENDAPATAN DAN KONSUMSI DI KELURAHAN SINDANG SARI KECAMATAN SAMBUTAN (Analysis of Household Welfare of Lowland Paddy Farmer based on Income and Consumption in Sindang Sari Urban Village Sambutan Subcity) - FELYSA SANTIKA SARAGIH; RITA MARIATI (Universitas Mulawarman (University of Mulawarman), 2020)
The level of income and household consumption reflects the welfare level of farmer household of lowland paddy. The purposes of this study were to know the income of lowland paddy farming, the income of farmer household, the consumption of farmer household, and the welfare level of farmer household. This study was conducted from April to June 2018 in Sindang Sari Urban Village, Sambutan Subcity. Data analysis was done to calculate of total cost, revenue, income, consumption, and welfare of farmer household of lowland paddy. The result of this study showed the average income of lowland paddy farming in Sindang Sari Urban Village, Sambutan Subcity was IDR10,674,523.81 ha-1 cropping season-1. The average income of farmer household in that the urban village was IDR28,623,380.95 year-1. The average household consumption of farmer household was IDR24,535,257.14 year-1. The average per capita income of lowland paddy farmer was IDR13,697,175.95 capita-1 year-1. Based on the welfare level of farmer household of lowland paddy was known if 85.71% respondents above the poverty line and 14.29% below the poverty line.